Novel amidrazone derivatives: Design, synthesis and activity evaluation. Issue 12 (23rd July 2018) - Zhou, Hua; Wang, Zhi Sen; Liu, Xin Hua; Chen, Fei Hu
Graphical abstract: Highlights: Novel naphthalenes as selectivity ASIC1a inhibitors were designed. Results revealed compound 5e showed activity to inhibit [Ca 2+ ]i . Compound 5e evaluated as potential ASIC1a inhibitor. Abstract: A series of new 6-styryl-naphthalene-2-amidrazone derivatives were synthesized and evaluated as potential ASIC1a inhibitors. Among them, compound 5e showed the most activity to inhibit [Ca 2+ ]i . elevation in acid-induced articular chondrocytes. Together with the important role of ASIC1a in the pathogenesis of tissue acidification diseases including rheumatoid arthritis, these results might provide a meaningful hint or inspiration in developing drugs targeting at tissue acidification diseases.